Change in individuals without a name. Contextual indicators & the free change-adaptive logic - Vanackere, Guido (Logic and Logical Philosophy, 2003)
Proof theory and semantics of an adaptive logic that deals adequately with change in individuals with or without a name are presented. New logical constants are introduced, viz. indicators. Within a given context they function as names, predicates and quantifiers at the same time. The thus extended language (of classical logic) has a big expressive power and solvespartly — the (classical) non-logical presuppositions with respect to ‘the existence of individuals’. Nevertheless, from a purely logical point of view, the here pre - sented logic requires nothing but a very intuitive selection of classical models of the premises, viz. the minimally abnormal ones.